Aid to developing-country agriculture: investing in poverty reduction and new export opportunities - Pinstrup-Andersen, Per; Cohen, Marc J. (International Food Policy Research Institute, 1998)
Asia’s economic crisis continues to reverberate globally, demonstrating the pivotal place of developing countries in world trade. It is now well established, if counterintuitive, that broad-based agricultural growth in developing countries boosts their agricultural imports. Aid can play a catalytic role in agriculture-led growth, but developing-country governments bear primary responsibility. They must create and maintain rural infrastructure; facilitate small farmers’ access to inputs and credit; invest in agricultural research, basic education, primary health care, and nutrition; and offer incentives to protect natural resources.